2011
DOI: 10.1530/eje-10-1096
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose metabolism in Japanese patients with acromegaly is restored after successful pituitary surgery if pancreatic β-cell function is preserved

Abstract: Objective: Impaired glucose metabolism is common in acromegaly, but it is not clear how glucose metabolism is impaired or what predicts its restoration after cure of the disease. To identify factors involved in the impairment of glucose metabolism in acromegaly, we evaluated clinical parameters before and immediately after surgical cure of the disease. Design and methods: We retrospectively analyzed clinical data of 92 consecutive Japanese patients with acromegaly who underwent successful pituitary surgery. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 16 publications
10
39
1
Order By: Relevance
“…Further, HOMA-%b, which is an index of basal insulin secretion, was 80G46 after surgery in patients with histories of ketoacidosis. Both parameters were similar to those observed in postsurgical acromegaly subjects who had impaired glucose metabolism before surgery and normalized glucose metabolism following complete pituitary adenomectomy (33). Thus, intrinsic insulin secretion in the patients presented here seemed to be preserved after surgery.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Further, HOMA-%b, which is an index of basal insulin secretion, was 80G46 after surgery in patients with histories of ketoacidosis. Both parameters were similar to those observed in postsurgical acromegaly subjects who had impaired glucose metabolism before surgery and normalized glucose metabolism following complete pituitary adenomectomy (33). Thus, intrinsic insulin secretion in the patients presented here seemed to be preserved after surgery.…”
Section: Discussionsupporting
confidence: 85%
“…As we reported previously (33), normal glucose metabolism was restored in a subset of patients who underwent surgery for acromegaly. In that report (33), we divided acromegaly patients into three groups according to their glucose tolerance before and after surgery.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been suggested that impaired glucose metabolism is mediated by growth hormone (GH)-induced insulin resistance. Several studies have suggested that insulin resistance contributes to abnormal glucose tolerance in acromegalic patients (6-8), but Kasayama et al (9) reported that impaired β-cell function is important in determining the glucose tolerance status in acromegalic patients, and Kinoshita et al (10) reported that once β-cell function is impaired, abnormal glucose metabolism persists even after patients have been cured of acromegaly. Therefore, both insulin resistance and pancreatic β-cell dysfunction appear to be involved in the pathogenesis of glucose homeostasis abnormalities in acromegalic patients.…”
Section: Introductionmentioning
confidence: 99%
“…If the compensatory hyperfunction of pancreatic β-cells does not counterbalance the reduced insulin sensitivity, abnormal glucose tolerance is likely to become clinically evident [18]. Kinoshita et al [19] reported that abnormal glucose tolerance fails to normalize after acromegaly has been cured once the function of the pancreatic β-cells has been impaired. In the present case, the insulinogenic index suggested that the impairment in insulin secretion persisted after surgery.…”
Section: Discussionmentioning
confidence: 99%